Protocol for salt stress screening of African marigold under hydroponic system - PAIKARAY, A K; KUMAR, PRABHAT; RAJU, D V S; SINGH, KANWAR PAL; GOPALAKRISHNAN, S; SHARMA, V K; JAIN, RITU (The Indian Journal of Agricultural Sciences, 2021)
The present study was carried out at ICAR-IARI to standardize the protocol for screening of African marigold against saline stress under hydroponic system. Seedlings of African marigold cv. Pusa Narangi Gainda were grown under hydroponics system. They were treated with different levels of NaCl, viz. 0 mM 50 mM, 80 mM, 100 mM, 120 mM, 140 mM, 150 mM, 160 mM, 200 mM, after 7 days of transplanting to standardize the threshold level for the further rapid screening of germplasms at nursery stage. Observations on mortality, growth, morphological, physiological, biochemical parameters and tissue nutrient status were recorded and found to decrease with increasing in saline stress. Mortality in seedlings was not observed up to 80 m M NaCl stress. 150-160 mM qualified as the indicator concentration for the screening of African marigold genotypes based on the performance of marigold genotypes with regard to different morphological, physiological, biochemical parameters and tissue nutrient contents.